Can Liquid Lenses Increase Depth of Field in Head Mounted Video See-Through Devices? - Marina Carbone; Davide Domeneghetti; Fabrizio Cutolo; Renzo D’Amato; Emanuele Cigna; Paolo Domenico Parchi; Marco Gesi; Luca Morelli; Mauro Ferrari; Vincenzo Ferrari (Journal of Imaging, 2021)
Wearable Video See-Through (VST) devices for Augmented Reality (AR) and for obtaining a Magnified View are taking hold in the medical and surgical fields. However, these devices are not yet usable in daily clinical practice, due to focusing problems and a limited depth of field. This study investigates the use of liquid-lens optics to create an autofocus system for wearable VST visors. The autofocus system is based on a Time of Flight (TOF) distance sensor and an active autofocus control system. The integrated autofocus system in the wearable VST viewers showed good potential in terms of providing rapid focus at various distances and a magnified view.